FM band channel measurements and modelling - Ahmadin, Omar Mohamed Mohamed Ibrahim (İstanbul Medipol Üniversitesi Fen Bilimleri Enstitüsü, 2018)
As the demand for higher data rates increases every day, the need for new frequency bands becomes more and more prominent. The FM band between 88 and 108 MHz is one of the bands that are not fully utilized. This band for now is being assigned for audio broadcast around the world, however, it is expected that more people will abandon the services offered at this band. The band is characterized by great features. For instance, it retains exceptional key characteristics such as propagation, which has a large coverage range and excellent through-buildings penetration. As FM coverage is so ever-present around the world, various applications can be considered to better exploit this useful band. Thus, investigating and obtaining the key channel parameters for the FM band for the possible two-way digital wireless systems, has become of significant interest. In this thesis, we present the results of field measurements at 86 MHz conducted at Gebze, Kocaeli, Turkey. Through the measurements, some of the FM channel characteristics are identified. Measurements are performed for urban, hilly terrain, and rural areas. Our results show that the FM channel expectedly has a large coverage area but at the same time, it possesses large channel excess delays. While most of COST-207 channel power delay profile models are also applicable for the FM Band, for urban environments and hilly terrain environments, channel clusters and excess delays are also higher than those of COST-207 models. As 5G systems aim to utilize lower frequency bands for supplementary links, FM Band can be considered as one of the potential bands and the channel models proposed in this study can then be exploited for performance analysis.

Daha yüksek veri hızlarına olan talep her geçen gün arttıkça, yeni frekans bant-larına olan ihtiyaç da daha belirgin hale gelmektedir. Frekans modülasyon (FM)bandının 88 ve 108 MHz arası tam olarak kullanılmamış bantlardan biridir.Şimdilik bu bant dünya genelinde ses yayını için tahsis edilmiştir, ancak dahafazla insanın bu bantta sunulan hizmetleri terk etmesi beklenmektedir. Bu bant harika özellikler barındırmaktadır. Örneğin, bu bant geniş bir kapsama alanı ve mükemmel bina içi penetrasyonu sağlayan yayılım gibi önemli bir özelliğe sahiptir. Dünyada FM kapsama alanı her zaman mevcut olduğundan, çeşitli uygulamaların bu faydalı banttan daha iyi yararlanması gerektiği düşünülmelidir. Böylece, FM bandında olası iki yönlü dijital kablosuz sistemler için ana kanal parametrelerinin araştırılması ve elde edilmesi önemli bir hale gelmiştir. Bu tezde, biz Türkiye Kocaeli ilinin Gebze ilçesinde 86 MHzâ??de saha ölçüm sonuçlarını sunmaktayız. Ölçümler sayesinde, FM kanalı özelliklerinden bazıları belirlendi. Ölçümler kentsel alanlarda, engebeli arazilerde ve kırsal alanlarda yapıldı. Elde etiğimiz sonuçlar, FM kanalının geniş bir kapsama alanına sahip olduğunu ve aynı zamanda fazla kanal gecikmesine (excess delay) sahip olduğunu göstermiştir. COST-207â??nin kanal gücü gecikme profili modellerinin çoğu kentsel ve engebeli arazi ortamları için geçerliyken, kanal kümeleri (clusters) ve gecikmeleri COST-207 profil modellerinden daha yüksektir. 5G sistemlerinde ek bağlantılar için düşük frekans bantlarının kullanılması amaçlandığından, FM bandı potansiyel bantlardan biri olarak düşünülebilir ve bu çalışmada önerilen kanal modelleri daha sonra performans analizi için yararlanılabilir
FM bandı kanal ölçümleri ve modellenmesi
Keywords: Channel Measurements; Channel Sounding; Channel Impulse Response; Power Delay Profile; Direction of Arrival; Doppler Spread; Rician Kfactor; Path Loss; Kanal Ölçümleri; Kanal Sesi; Kanal Darbe Yanıtı; Güç Gecikme Profili; Varıs Yönü; Doppler Yayılımı; Rician K-faktör; Yol Kaybı